Relationship between Coaches’ Leadership Style and Athletes’ Satisfaction toward Coach and Sports Performance Satisfaction at National and Provincial Levels - Dinda Pinkan Melati; Agus Rusdiana; Iwa Ikhwan Hidayat (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2025)
This study aims to determine the relationship between coaches’ leadership style and athletes’ satisfaction toward their coach and sports performance satisfaction among junior athletes at the national and provincial levels in West Java. The research employed a quantitative descriptive approach with an associative survey design. The sample consisted of 47 athletes enrolled in the Sentra Pembinaan Olahragawan Berbakat Nasional (SPOBNas) and Satuan Pendidikan Olahragawan Daerah (SPOBDA) of West Java, selected through purposive sampling. Research instruments included the Leadership Scale for Sports (LSS), Satisfaction Scale for Athletes (SSA), and Athlete’s Subjective Performance Scale (ASPS). Data were analyzed using Spearman’s Rank correlation test with a significance level of 0.05. The results revealed a strong and significant positive relationship between the coach’s leadership style and athletes’ satisfaction toward the coach (rₛ = 0.684; p < 0.01), but no significant relationship between leadership style and satisfaction toward sports performance (rₛ = 0.151; p > 0.05). These findings indicate that coaches’ leadership plays a crucial role in shaping athletes’ interpersonal satisfaction, whereas performance satisfaction is more influenced by internal factors such as motivation and personal experience. The study highlights the importance of adopting adaptive, participative, and humanistic leadership styles in the coaching of young athletes.